Recurrent diffuse lung disease due to surfactant protein C deficiency. (2018) - Kazzi, Brigitte; Lederer, David; Arteaga-Solis, Emilio; Saqi, Anjali; Chung, Wendy K.
Abstract: Surfactant protein C (SP-C) deficiency causes diffuse lung disease with variable prognosis and severity that usually presents in infancy. We present the case of a patient with diffuse lung disease who was successfully treated with hydroxychloroquine and steroids in infancy, who presented again as a young adult with respiratory symptoms. Exome sequencing identified a novel de novo SFTPC mutation (c.397A > C p.S133R). Mutated SP-C accumulates and leads to injury of alveolar type II cells, which normally replenish alveolar type I cells after injury. This may explain the symptom recurrence after lung injury in young adulthood. Although hydroxychloroquine has been hypothesized to interfere with mutated SP-C accumulation, data on long term outcome remains limited.